Design and fabrication of an IoT-based smart electrical meter for residential energy management - Thanh Ba Nguyen; Tri Cao Nguyen (Institute of Advanced Engineering and Science, 2023)
Transparency in electricity measurement and efficient use of electricity are issues of concern to households. Electricity customers want to have confidence in their utility company's electricity meters installed at their houses. This study designs and constructs an internet of things (IoT)-based smart electric meter to measure electricity and remotely control domestic appliances. This device can monitor, calculate electricity bills and remotely control the appliances via the internet; electrical quantities are displayed in real-time on the Blynk app, liquid crystal display (LCD) screen and Google Sheet. The device is also capable of emailing the electricity user. The proposed system is designed and developed based on ESP32, a LCD, a PZEM 004T, four relays and a DC source. The results show that the device works stably and the device’s error is less than 5%. This research makes it possible for users to conveniently monitor their power consumption while enhancing their energy-saving awareness.